2021
DOI: 10.1002/anie.202104114
|View full text |Cite
|
Sign up to set email alerts
|

Sub‐Second Time‐Resolved Surface‐Enhanced Raman Spectroscopy Reveals Dynamic CO Intermediates during Electrochemical CO2 Reduction on Copper

Abstract: The electrocatalytic carbon dioxide (CO 2 )reduction reaction (CO 2 RR) into hydrocarbons is apromising approach for greenhouse gas mitigation, but many details of this dynamic reaction remain elusive.Here,time-resolved surface-enhanced Raman spectroscopy( TR-SERS) is employed to successfully monitor the dynamics of CO 2 RR intermediates and Cu surfaces with sub-second time resolution. Anodic treatment at 1.55 Vvs. RHE and subsequent surface oxide reduction (below À0.4 Vv s. RHE) induced roughening of the Cu e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
162
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(197 citation statements)
references
References 86 publications
(55 reference statements)
11
162
0
Order By: Relevance
“…1,2 The adsorption and catalytic conversion of CO 2 to valuable chemicals and fuels would be an ideal solution to decrease the CO 2 concentration in the atmosphere and alleviate the energy shortage. 3,4 Compared with other catalytic conversion methods, the CO 2 electroreduction reaction (CO 2 RR) using renewable energy resources for electricity can convert CO 2 to various value-added chemicals under mild and clean conditions. 5–11 Compared with other products, the two-electron involved product CO that has been widely used to produce synthetic liquid fuels by the Fischer–Tropsch process may be more easily produced via the CO 2 RR.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The adsorption and catalytic conversion of CO 2 to valuable chemicals and fuels would be an ideal solution to decrease the CO 2 concentration in the atmosphere and alleviate the energy shortage. 3,4 Compared with other catalytic conversion methods, the CO 2 electroreduction reaction (CO 2 RR) using renewable energy resources for electricity can convert CO 2 to various value-added chemicals under mild and clean conditions. 5–11 Compared with other products, the two-electron involved product CO that has been widely used to produce synthetic liquid fuels by the Fischer–Tropsch process may be more easily produced via the CO 2 RR.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Various studies have managed to verify the importance of the catalyst hydrophobicity, such as building a hydrophobic hierarchical structure, 16 and combining catalysts with a hydrophobe, creating a hydrophobic catalyst microenvironment. 7,14,17–20 These studies demonstrated the significant role of the balanced triple-phase in gas-involving electrochemical reactions. Nevertheless, much remains to be explored towards the optimal design with integrated efficient mass transfer and high ion conductivity.…”
mentioning
confidence: 94%
“…Another peak located at B 536 cm À1 appeared at potentials below À0.3 V, which was assigned to CuO x /(OH) y mixed phase. 19,23 Raman signals emerged at B301 cm À1 (P1) and B394 cm À1 (P2), corresponding to the restricted rotation of adsorbed CO, Cu-CO stretching, respectively, and the intensity ratio of P2/P1 is a valid indicator of surface coverage of CO (Fig. 4a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, a more energy-efficient and environmentally friendly process is desired. [3] Non-oxidative dehydrogenation of ethane is thermodynamically limited and generally carried out at high temperatures to achieve high conversion rates accompanied by undesirable coke production. [4] Oxidative dehydrogenation of ethane can overcome thermodynamic limitations and proceed at a lower temper-ature.…”
mentioning
confidence: 99%